KONSEPTUALISASI STRATEGI PEMBERDAYAAN EKONOMI MASYARAKAT DESA - Aji Fany Permana (J-EBI (Jurnal Ekonomi Bisnis Islam), 2021)
In the era of regional autonomy today, the development of rural areas occupies an urgent scale. Urgency is caused by the structure of the rural economy in general being in a disadvantage compared to the structure of the urban economy. This disproportionate situation has implications for socio-economic problems, such as inequality in the level of welfare of urban and rural communities, population density and urbanization in urban areas, which increases sharply from year to year. Therefore, how to grow and develop the economy in rural areas through the economic empowerment of its people to achieve harmony or equality with urban areas is a chore that needs to be answered immediately, especially by governments at the rural level.